PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, FREE CASH FLOW, CORPORATE GOVERNANCE DAN ASSETS GROWTH TERHADAP KEBIJAKAN DIVIDEN - Norma Wati; Buyung Sarita; Riski Amalia Madi; Ibnu Hajar; Wahyuniati Hamid (Jurnal Manajemen dan Kewirausahaan, 2022)
This study aims to examine the effect of profitability, liquidity, leverage, free cash flow, corporate governance and asset growth on dividend policy. The object of this research is 181 the manufacturing company listed on the Indonesia Stock Exchange for the 2015-2019 period. Sample selection was determined by purposive sampling method. In total, there are 24 companies that meet the research criteria. This study uses secondary data which was analyzed using panel data regression analysis and processed using application review 9.  The results of this study indicate that asset growth has a positive and significant effect on the dividend payout ratio, meaning that asset growth is able to increase dividend distribution. Furthermore, the return on assets and the current ratio have a negative and significant effect, meaning that an increased return on assets and current ratio will reduce the distribution of dividends. The debt-to-asset ratio has a negative and insignificant effect, meaning that a high debt-to-asset ratio is not able to reduce dividend distribution. The audit committee has a positive and insignificant effect on the dividend payout ratio, meaning that a high audit committee is not able to increase dividend distribution. Furthermore, free cash flow has a positive and insignificant effect on the dividend payout ratio, meaning that high free cash flow is not able to increase dividend distribution to shareholders.